Escolas multisseriadas de Rio Bananal/ES : ressignificando concepções e reinventando práticas pedagógicas - Picoli, Alessandra Altoé Ferreira (2024)
This dissertation study belongs to the Professional Postgraduate Program in Education of the Federal University of Espírito Santo, in the area of Concentration: Educational Practices, Diversity and School Inclusion. Its central intention is to understand the Multigrade Schools of the Countryside as a concrete possibility of guaranteeing the right of students to a quality education in/from the countryside, identifying the challenges that arise in the practices of teachers of the Multigrade Schools of the Municipality of Rio Bananal, in Espírito Santo (ES). The research was developed in the Multigrade Schools of the Countryside – Elementary Education – initial years, of the municipality of Rio Bananal/ES, initially involving 28 teachers. In this journey, we sought to base ourselves on the pertinent dialogues between Freire (1987, 1996), who presents education as an intervention capable of transforming realities in a meaningful, democratic, reflective and supportive way, ultimately, humanizing, enabling the emancipation of students; Caldart, Kolling and Cerioli (2002), whose work organized by them brings contributions related to Rural Education aimed at rural communities; Arroyo and Fernandes (1999), who present considerations regarding education in the context of multi-grades and, last but not least, the book organized by Antunes-Rocha and Hage (2015), which expresses the reality of Multi-grade Schools in the countryside. Regarding the methodology, it was decided to develop a qualitative research. To this end, bibliographic research, participant observation, field diary and questionnaire with closed and open questions were used. The purpose of this research was to understand the challenges faced by educators in Multi-grade Schools in the countryside, in the municipality of Rio Bananal. The results brought significant points, among which the lack of initial and continuing training to teach in multi-grade classrooms and the recognition of this need by the teachers stood out. Analyzing the context of the responses and with the aim of contributing, the educational product consists of a training proposal for teachers who work in the Multigrade Schools of the Countryside. A dialogic training that provides the participants with the opportunity to learn about the history of Rural Education and Freire's concepts involving humanization, problem-solving education, dialogue and generating themes. Furthermore, through practical activities resulting from these meetings, it enables reflection and reinvention of practice, based on the perception of contradictory situations in daily teaching practice in the classroom. Thus, it is expected that the provocation arising from the training will awaken a critical, dialogic and emancipatory educational vision, in which there is the possibility of work that approaches the concepts addressed, favoring the humanizing training of students in the Multigrade Schools of the Countryside, in the municipality of Rio Bananal